SCIENTIFIC SOCIALISM IN THE INHERITANCE LAW IN SOMALIA - Qurratul Uyun; Madah Rahmatan (IAIN Bone, 2022)
This paper discusses the influence of scientific socialism ideology on Islamic inheritance law in Somalia which is regulated in The Family Code 1975. This paper begins with a discussion of scientific socialism as a state ideology, then its influence on Islamic family law in Somalia and the application of scientific socialism ideology in inheritance law. The method used is descriptive with a theoretical approach that is explored through information media. The results of this study indicate that the deviation of family law regulations in Somalia from what is described in the Qur'an begins based on the concept of a state of scientific socialism that they apply. The purpose of implementing the ideology of scientific socialism in Somalia was to shift rigid customary rules and as a form of political cooperation with the Soviet Union. As a result, the application of the rules of family law has changed, especially in terms of inheritance. For example, there is no difference in the share of inheritance between husband and wife, sons and daughters, grandfather and grandmother, father and mother, even siblings, and half-siblings.